The use of direct oral anticoagulants in patients with ventricular assist devices: Is there hope for Factor Xa inhibition?. Issue 5 (8th March 2021) - Meredith, Thomas; Schnegg, Bruno; Hayward, Christopher
Abstract: The use of continuous‐flow ventricular assist devices (cf‐VAD) necessitates systemic anticoagulation, routinely with vitamin K antagonists (VKA). Newer direct oral anticoagulants (DOACs) have significant advantages over VKA in providing a predictable level of systemic anticoagulation without frequent monitoring or strict dietary surveillance. Despite randomized evidence demonstrating their usefulness in several conditions including atrial fibrillation, there is limited data pertaining to their use in cf‐VAD patients. Early reports of adverse outcomes has resulted in a Class III recommendation, advising against DOACs generally in cf‐VAD patients. Recent reports suggest there may be a role for certain DOACs; as such we present a systematic review identifying studies reporting DOAC uses in patients with a cf‐VAD. We identified eight pertinent studies, including a single randomized controlled trial and seven case reports/series. Limited numbers and significant study heterogeneity limits interpretation; however, Factor Xa inhibitors appear to be feasible alternatives, favorable to direct thrombin inhibitors, although further research is required. Abstract : Bleeding and thrombotic complications in the context of therapeutic anticoagulation account for significant morbidity amongst patients with ventricular assist devices. Observational data in this population suggest that these complications occur infrequently when direct oral anticoagulants are used in lieu of conventional vitamin K antagonists, though at present there are no randomised data assessing the safety and efficacy of these agents.